Perceptions Towards English Education Program Offered by Open and Distance Education Centre at Tribhuvan University: A CIPP Evaluation - Bhusal, Durga Raj; Bhandari, Laxman Prasad (Studies in ELT and Applied Linguistics, 2025)
The evaluation system of university education has drawn increasingly significant attention to greater accountability and enhancement of student learning outcomes, as well as the overall effectiveness of educational programs in achieving their intended objectives. Using Stuffle beam's context, input, process, and product (CIPP) Model (1983), this study evaluates the Master’s of Education (M.Ed.) English Program offered by the Open and Distance Education Centre (ODEC) at Tribhuvan University. Employing case study inquiry as a research methodology, the study delves deep into exploring teachers and students’ perceptions and practices through unstructured interviews with four teacher and student participants. Data collected from interviews were transcribed, coded, and analyzed using qualitative content analysis techniques outlined by Schreier (2012) and thematic analysis methods proposed by Braun and Clarke (2006). The findings highlight that the primary motive for choosing an open and distance learning program is the opportunity to pursue a degree while continuing a job for the students. Furthermore, the ODEC found emphasizing the delivery of quality education through relevant coursework and effective teaching strategies aiming to enhance knowledge and pedagogical expertise in English language education. However, participants revealed several challenges, including their inefficiency in using technological devices, excessive workloads, unreliable electricity and internet connectivity, and the requirement to attend traditional pen-and-paper assessments at the end of each semester, among others. Consequently, the study recommends that the evaluation system be adapted to accommodate the geographical diversity of students, their employment commitments, and technological limitations, thereby ensuring greater flexibility and accessibility.